2021
DOI: 10.7759/cureus.14514
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Are the Elderly With Diabetes Mellitus Type 2 Prone to Fragility Fractures?

Abstract: Diabetes mellitus type 2 (T2DM) is an emerging public health issue with high prevalence rates among older adults while fragility fractures constitute a significant public health burden with a great impact. Osteoporosis is the most important metabolic bone disease in patients with diabetes mellitus. Based on current evidence, individuals with T2DM are more vulnerable to fragility fractures than their non-diabetic counterparts, although until now, there aren't any systematic reviews or meta-analyses concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Studies have indicated that individuals diagnosed with type 2 diabetes are at an increased risk of developing osteoporosis. At the same time, compared with general age-related osteoporosis, patients with type 2 diabetes osteoporosis tend to be more susceptible to bone fragility due to prolonged exposure to a high-glucose environment [ 3 ]. Hence, as the global population ages, the severity of the situations regarding type 2 diabetic osteoporosis will also increase [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that individuals diagnosed with type 2 diabetes are at an increased risk of developing osteoporosis. At the same time, compared with general age-related osteoporosis, patients with type 2 diabetes osteoporosis tend to be more susceptible to bone fragility due to prolonged exposure to a high-glucose environment [ 3 ]. Hence, as the global population ages, the severity of the situations regarding type 2 diabetic osteoporosis will also increase [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 T2DM combined with osteoporosis can increase the complexity and severity of the patient’s condition, affect health, and reduce quality of life. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…The current treatment methods for T2DM combined with osteoporosis mainly include blood glucose control, calcium and Vitamin-D supplementation, and exercise therapy. 5 - 7 For severe osteoporosis, medication such as bisphosphate can be considered. 7 , 8 Calcium plus Vitamin-D supplements increase calcium and Vitamin-D3 levels, thus promoting bone formation and increasing bone density.…”
Section: Introductionmentioning
confidence: 99%
“…10 A systematic review of 17 studies demonstrated an increase in the prevalence of low-energy hip fractures for older adults with DM compared with those without DM. 11 A cohort study of older adults in Taiwan revealed that the risk of hip fracture was greater for patients with DM compared with those without, regardless of a patient's body mass index. 12 Hip fractured patients with DM needed longer rehabilitation following surgery and had lower functional outcomes after rehabilitation as compared with non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Age is a risk factor for hip fracture and diabetes mellitus (DM) can also increase hip fracture risk and complications due to abnormal bone metabolism 10 . A systematic review of 17 studies demonstrated an increase in the prevalence of low‐energy hip fractures for older adults with DM compared with those without DM 11 . A cohort study of older adults in Taiwan revealed that the risk of hip fracture was greater for patients with DM compared with those without, regardless of a patient's body mass index 12 .…”
Section: Introductionmentioning
confidence: 99%